2007
DOI: 10.1163/156856107781192346
|View full text |Cite
|
Sign up to set email alerts
|

The curing performance of UV-curable semi-interpenetrating polymer network structured acrylic pressure-sensitive adhesives

Abstract: This article reports on the curing performance of UV-curable acrylic binders prepared with trifunctional monomers and a photoinitiator. The curing reaction was achieved by direct excitation of pressure-sensitive adhesives (PSAs) by irradiation with a 100-W high-pressure mercury lamp with different UV doses. The curing performance of PSAs was studied by photo-differential scanning calorimetry (photo-DSC), gel-fraction determination and Fourier transform infrared-attenuated total reflection (FTIR-ATR) spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…(photo-DSC) The reaction rate can be measured by monitoring the rate at which heat is released from a polymerizing sample, because polymerization is generally an exothermic reaction. Therefore, the profiles of the heat of reaction versus time, obtained by photo-DSC, can be used to characterize reaction kinetics and evaluate polymerization rate constants [30]. The crosslinking sites that remain after primary curing cause an exothermic reaction when exposed to UV during secondary curing.…”
Section: Results and Discussion 31 Photo-differential Scanning Calomentioning
confidence: 99%
“…(photo-DSC) The reaction rate can be measured by monitoring the rate at which heat is released from a polymerizing sample, because polymerization is generally an exothermic reaction. Therefore, the profiles of the heat of reaction versus time, obtained by photo-DSC, can be used to characterize reaction kinetics and evaluate polymerization rate constants [30]. The crosslinking sites that remain after primary curing cause an exothermic reaction when exposed to UV during secondary curing.…”
Section: Results and Discussion 31 Photo-differential Scanning Calomentioning
confidence: 99%
“…These results are the similar to the general trend of UV curable adhesive. [5][6][7] 2-CEAP shows no inclination results which include fibrillation phenomenon in the entire section. Based on these results, AA showed superior results for application to self-cure adhesive material adhesive.…”
Section: Probe Tackmentioning
confidence: 94%
“…Our research group reported on the crosslinking performance of the IPN system composed of acrylic binders, tri-functional monomers and a photo-initiator 6) . is formed using TMPTA shown in Fig.…”
Section: Conventional Approach Of Uv Curingmentioning
confidence: 99%